Understanding impacts of water supplementation in a heterogeneous landscape - Farmer, Helen (My University, 2011)
Artificial water provision is a contentious management issue in southern African savanna conservation areas. Supplementation of permanent water leads to higher herbivore population sizes which can generate greater profits. However, water supplementation can lead to detrimental effects on soils and vegetation surrounding waterpoints. Currently, the impact of artificial waterpoints across properties is understood in terms of the piosphere model: concentric circles with differing degradation levels, focused on waterpoints. Southern African savannas are highly heterogeneous so the suitability of a homogeneity based approach in management is questionable. Provision of water currently follows a relatively high degradation risk strategy on many properties so a sound basis for management is essential. This study assessed the general applicability of the piosphere model by testing the relationship between distance to water and ecological variables (soil functionality and herbaceous and woody vegetation). 23 variables were tested across 22 waterpoints from five properties within the Great Limpopo Transfrontier Conservation Area. Statistical approaches used matched those of previous piosphere studies but only 14% of tests were significant. Although utilisation gradients were found for some variables and some transects, there was no generally applicable pattern. This means that results from previous piosphere studies cannot be transferred to unsampled waterpoints or scaled up across properties. The level of heterogeneity in southern African savannas disrupts the piosphere pattern to such an extent that the model does not form an appropriate basis for management. In order to develop an alternative approach to understanding the functionality of properties which takes into account both water supplementation and heterogeneity, the influence of a range of environmental and management variables on degradation and species composition were tested using ordinations. The best explanation of variation was a combination of environmental and management variables. Broader scale variables such as natural and artificial water availability were more important than finer scale variables such as distance to water. These results were used to develop a basic approach to evaluating property functionality.